Intestinal stoma in patients with colorectal cancer from the perspective of 20-year period of clinical observation - Banaszkiewicz, Zbigniew; Woda, Łukasz P.; Zwoliński, Tomasz; Tojek, Krzysztof; Jarmocik, Paweł; Jawień, Arkadiusz (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Introduction : Intestinal stoma is a procedure most often performed in patients with colorectal cancer. Aim : To identify the percentage of patients with colorectal cancer in which the intestinal stoma was performed. Material and methods : We retrospectively analysed 443 patients treated during a 20-year period (1994–2013) due to colorectal cancer, in which the intestinal stoma was made during the first surgical intervention. Results : In the second analysed decade, a significant decrease in the percentage of created stomas, definitive stomas in particular, was observed. Stomas were made significantly more often in patients with a tumour located in the rectum, the left half of the colon, and in patients undergoing urgent surgeries. An increased incidence of intestinal stomas was associated with a higher severity of illness and higher proportion of unresectable and non-radical procedures. The definitive stomas were significantly more often made in men and in patients with tumours located in the rectum, whereas temporary stomas were created significantly more often in patients undergoing urgent operations. Conclusions : In the last decade (2004–2013) the number of intestinal stomas in patients operated due to colorectal cancer was significantly reduced.